Persepsi Masyarakat Sekitar Terhadap Keberadaan Lokalisasi PSK Batu Merah Tanjung Kecamatan Sirimau Kota Ambon - Laka, Beatus Mendelson (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to determine the perception of the surrounding community on the existence of localization of PSKBatu Merah Tanjung, Sirimau District, Ambon City. When viewed from the objective, this type of research isdescriptive qualitative research, this research is descriptive analytic research. The data collection techniques used inthis study were observation, interviews, questionnaires and documentation. As for the determination of informants,researchers used random sampling techniques or random samples, according to the level of education of the head ofthe family who lives in the brothel as a respondent to provide supporting information in strengthening informationfrom the community. The results showed that the perception of the community around the localization of PSK BatuMerah Tanjung, most of the residents had a tendency to have almost the same perception, that is, each of themtended to have a positive perception, in seeing the existing settlement conditions. This can be seen from theperception of the surrounding community towards the existence of the localization of PSK Batu Merah Tanjung has agood social life between CSWs and the surrounding community and vice versa, the community with CSWs. This isevident when every environmental service program programmed by the local RT, is always involved with CSWs withcommunity members. From the explanation above, women who work as CSWs also have the same social spirit as thesurrounding community, and what distinguishes CSWs from the surrounding community is the perception of beingCSWs used by the community, which is seen from the social relations between the local community and CSWs. Sothat the people who live around the prostitution area are very happy with the existence of CSWs. This is strengthenedby the results of direct interviews with respondents who stated that most of the people living around the TanjungBatu Merah lokalisasi are mostly immigrants such as the Bugis, Buton, Makassar and Batu Merah villagersthemselves who are married to immigrant communities such as the Bugis, Buton and Makassar.